Jiwa / Muhammad Shafiq Ilham Azman ... [et al.] - Azman, Muhammad Shafiq Ilham; Mohd Nizam, Siti Norsyaurah; Muhamad Alwi, Siti Suhana; Yuserrie, Farid Al Hakeem (2024)
For this design, this paper describes an integrative approach for the development of this project. This proposal also envisions a space design that is not merely a passive integration of concept, but an active participant in its cycle. By integrating public engagement with innovative yet classic architecture elements, we aim to create a structure that celebrates both the novelty of design and the beauty in functionality aspects, while exemplifying its sustainability value. This design is rooted in the concept of “Daun Sibar Dayang”, drawing inspiration from the diversity of traditional uniqueness of history and aesthetic appeal found in its natural form, that complement each other well. As the overall integration of the concept, all elements and forms reflect the design’s morphology. The space design fosters a sense of connection with nature as it is abundant with natural light and biophilic design elements, creating a serene atmosphere. By fusing traditional craftsmanship elements with cutting-edge technology, this project redefines the possibilities of wood architecture.